Iowa RBA, November 25, 1996 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1996)
Iowa RBA update for November 25, 1996. Highlights of the update include sightings of a Pomarine Jaeger, a Pacific Loon, numerous Snowy Owls, a first year Black-legged Kittiwake, and a Long-tailed Duck. Other notable observations were of a White-winged Scoter, two first year Glaucous Gulls, and a first year Thayer's Gull. Also included are handwritten notes for the next week's update with sightings of Red Crossbills and a female Surf Scoter. Epson - sheet feed/flatbed